Tuning of Multivariable PI Controllers by BLT Method for TITO Systems. Issue 4 (2nd April 2016) - Besta, Chandra Shekar; Chidambaram, Manickam
Abstract : The design of decentralized proportional integral (PI) controller based on biggest log modulus tuning (BLT) tuning method is extended to design centralized PI controllers for two-input–two-output (TITO) systems. The multivariable PI control structure proposed by Tanttu and Lieslehto (1991 ) is considered. The single detuning parameter (F) is selected in order to get the biggest log modulus as 4 dB. Decentralized PI controllers are also designed using the IMC to get the biggest log modulus as 4 dB. The centralized PI controllers give improved main responses and decreased interactions. This improvement is shown particularly for TITO systems having the relative gain element, λij < 1. The robustness of these controllers is evaluated by the inverse maximum singular value versus frequency plot for both the input and output multiplicative uncertainties. Simulation results are given for two TITO examples. The present controllers give better performances over that of the original Tanttu and Lieslehto (TL) method. The present decentralized PI controllers give improved performances over the decentralized PI controllers proposed by Xiong and Cai (2006 ).